Thermoelectric power generator for automotive applications - Akdogan, Volkan (2016)
A thermoelectric generator (TEG) converts thermal energy into electrical energy corresponding to temperature gradient across both hot and cold surfaces with a conversion efficiency of approximately 5%. In spite of the conversion efficiency, TEGs can be implemented effectively for waste heat recovery systems within the power rating of kilowatts. The insufficiency of natural resources, frequently increasing oil costs and emission regulations have become an incentive factor of the recent increased interest in TEG applications. This thesis introduces a practical implementation of the thermoelectric generator for an automotive exhaust system which has a rapid transient response to produce electrical energy from the waste heat which flows through the exhaust pipe. In addition to automotive TE power generator implementation, an H-Bridge DC-DC converter within the operation of maximum power point tracking method is introduced in this thesis to obtain the maximum power transfer between the thermoelectric power generator and the load. This thesis presents a transient solution to the two-dimensional heat transfer equation with variant ambient temperature that determines heat transfer and electrical potential across the thermoelectric pellet. This equation is applied into a designed two-dimensional heat transfer MATLAB model and a comparison of simulation and experimental results approves the accuracy of the designed model. In addition to heat transfer simulation, a dynamic large scale thermoelectric power generator simulation program is introduced in this thesis to provide data analysis of actual implementation.